Outcome measurement for orthopaedic trauma inpatients - E. Moghazy; Q. Louw (South African Journal of Physiotherapy, 2008)
In clinical physiotherapy, there is growing importance for theaccuracy and reliability of assessment and outcome measures. There are nooutcome measure instruments for orthopaedic trauma inpatients published inthe literature. This paper reports on the initial research to develop an outcomemeasure for orthopaedic trauma inpatients. Item generation was done by doinga systematic review of published functional outcome measures. Item reductionwas conducted by using a panel of physiotherapists and patients.  A  total of115 functional items were generated and this was reduced to 29 functionalitems deemed appropriate for othopaedic trauma inpatients. A lthough furtherpsychometric properties should now be tested, the draft outcome measure can serve as a guide in the education ofundergraduate students as well as to clinicians working in orthopedic trauma wards.